« Les brevets sont à peine au rang d’une publication » - Victoria Brun (Revue d'anthropologie des connaissances)
This article aims to clarify the place that valorization practices hold in the careers of public research staff, and the way in which they do or do not work to internalize them in the academic credibility cycle (Latour & Woolgar, 1979). The analysis is based on an inquiry carried out in valorization projects linked to the CNRS, and shows that valorization activities are thought of in conjunction with academic ones. Although researchers most often fail to convert them into recognition without detouring through publication, they can re-inject this investment in the form of funding and equipment for other work. Others decide to outsource it, making valorization a career sideline. Although doctoral students and engineers contribute to the credibility cycle of researchers, they invest in parallel professional paths. Finally, involvement in valorization projects exposes researchers to the risk of decredibilization that they avoid by defending a conception of scientific disinterestedness compatible with the application perspective. The transformation of the economy of credibility is therefore taking place at the margins, despite the many incentives provided by research institutions.